Conditions for Radiative Cooling and Collapse in the Plasma Focus Illustrated With Numerical Experiments on PF1000 - Lee, Sing; Saw, Sor Heoh; Akel, M.; Ali, Jalil; Kunze, Hans Joachim; Kubes, Pavel; Paduch, Marion (IEEE, 2016)
Reduced Pease–Braginskii currents are estimated for a linear pinch in a range of gases, namely, D, He, Ne, Ar, Kr, and Xe. A characteristic depletion time is defined as the time it takes for the plasma focus (PF) pinch energy to be radiated away. This quantity is used as an indicator for expectation of radiative collapse. The depletion times in various gases are estimated in units of pinch duration. The values indicate that in D and He, the radiation powers are small, resulting in such long depletion times that no radiative collapse may be expected in the lifetime of the focus pinch. In Ne, low tens of percent are radiated and significant cooling and reduction in radius ratio may be anticipated. In Ar, Kr, and Xe, the depletion time is only a fraction of the estimated pinch duration, so radiative collapse may be expected. Numerical experiments are then carried out with a circuit-coupled code, which incorporates radiation-coupled dynamics with PF pinch elongation and plasma self-absorption. The latter eventually limits the radiated power and stops the radiative collapse. These results show the detailed dynamics and confirm the expectations arising from depletion times discussed above.